2020
DOI: 10.7461/jcen.2020.22.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical treatment for the recurrent cerebral aneurysm initially treated using coil embolization

Abstract: Objective: Microsurgical treatment could be a good alternative for the treatment of recurrent cerebral aneurysm after coil embolization. The purpose of this study was to present our experience of microsurgical treatment for recurrent cerebral aneurysm previously treated using coil embolization. Methods: From June 2012 to May 2019, 34 patients consecutively received microsurgical treatment for a recurrent cerebral aneurysm previously treated using coil embolization after it ruptured. Results: Of the 34 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…5 There is no consensus on whether to remove the spring coil during aneurysm clipping. [8][9][10]22 Some scholars have used different combinations of clips or specially designed clips to clip the recurrent aneurysm after embolization, thereby avoiding the need to remove the spring coil. 21,22 For difficult-toclip recurrent aneurysms during surgery, some scholars have performed aneurysm wrapping.…”
Section: Surgical Management Of Recurrent Intracranial Aneurysmsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 There is no consensus on whether to remove the spring coil during aneurysm clipping. [8][9][10]22 Some scholars have used different combinations of clips or specially designed clips to clip the recurrent aneurysm after embolization, thereby avoiding the need to remove the spring coil. 21,22 For difficult-toclip recurrent aneurysms during surgery, some scholars have performed aneurysm wrapping.…”
Section: Surgical Management Of Recurrent Intracranial Aneurysmsmentioning
confidence: 99%
“…[8][9][10]22 Some scholars have used different combinations of clips or specially designed clips to clip the recurrent aneurysm after embolization, thereby avoiding the need to remove the spring coil. 21,22 For difficult-toclip recurrent aneurysms during surgery, some scholars have performed aneurysm wrapping. 8 In this study, 3 cases were treated by clipping the aneurysm by removing the spring coil, and one case was switched to extracranial-intracranial bypass due to the difficulty of removing the spring coil for clipping.…”
Section: Surgical Management Of Recurrent Intracranial Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, when considering retreatment, it should be recognized that recurrence of an aneurysm can have two distinct causes: aneurysm regrowth and coil compaction. Aneurysm regrowth is characterized by a change in the morphology of the aneurysm relative to its initial structure (9). Coil compaction is a change in the configuration of the coil compared with the baseline appearance of the coil mass after CE, without changes in the morphology of the aneurysm itself (9).…”
Section: █ Conclusionmentioning
confidence: 99%
“…Aneurysm regrowth is characterized by a change in the morphology of the aneurysm relative to its initial structure (9). Coil compaction is a change in the configuration of the coil compared with the baseline appearance of the coil mass after CE, without changes in the morphology of the aneurysm itself (9). It is important to differentiate between the two types of recurrence because some previous reports have found that aneurysm regrowth is more dangerous than coil compaction (2,11).…”
Section: █ Conclusionmentioning
confidence: 99%